Implicações de um programa de formação continuada na formação e atuação de professores de educação física atuantes no ciclo I - Guimarães, Jaqueline [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This work focused on research a course of continuing education for teachers of Physical Education, offered in a city of São Paulo in 2013. Adopting as a benchmark analysis of models of continuing education in teaching, investigative question that guided this study was: what are the implications of this formative process in the formation and performance of the participating teachers?. With this guiding question, four were the objectives we seek to respond to this analysis: first identify the profile of teachers as well as the participation and involvement of the same course developed; 2 map and analyze the manifestations of teachers throughout the course; 3 reflect on the role of teachers in relation to approaches and/or distances with the common physical education curriculum proposed by the municipality; 4 identify and analyze the reflections on the course conducted. The methodological approach was qualitative and eighteen participants were teachers of a school system in a city of São Paulo, active in cycle I (1 to 5 years) of primary school. Data collection was carried out in two phases, with the participants in the first stage seventeen teachers and three teachers in the second stage that in addition to acting in the cycle I also actively participated in the course. Data were obtained in phase one using a diagnostic interview recorded on voice recorder and transcripts of observations and recorded in video and voice recorder from sixteen meetings of the continuing education course conducted in 2013 and phase two included the observation of classes teachers in the 2nd half of 2013, ending with a final interview. Demonstrations of physical education teachers in the course, as well as the situations observed and interviews indicated that on the profile of teachers are in the age range 30-58 years to serve at least five years in schools and most (10) does not work elsewhere. Another observation is that most of the participating teachers when thes...

Este trabalho teve como foco de investigação um programa de formação continuada para professores de educação física, oferecido em uma cidade do interior de São Paulo no ano de 2013. Adotando como referência a análise dos modelos de formação continuada na docência, a questão investigativa que norteou este estudo foi: quais as implicações desse processo formativo na formação e atuação dos docentes participantes?. Com essa questão norteadora, quatro foram os objetivos que buscamos responder com essa análise: 1 identificar o perfil dos docentes, bem como, a participação e envolvimento dos mesmos no programa desenvolvido; 2 mapear e analisar as manifestações dos docentes ao longo do programa; 3 refletir sobre a atuação dos docentes em relação as aproximações e/ou distanciamentos com o currículo comum de educação física proposto por esse município; 4 identificar e analisar as reflexões sobre o programa realizado. A abordagem metodológica foi de natureza qualitativa e participaram desse estudo dezoito professores de um sistema de ensino de uma cidade do interior de São Paulo, atuantes no ciclo I (1º a 5º ano) do ensino fundamental. A coleta de dados desenvolveu-se em duas fases, tendo como participantes na primeira etapa dezessete professores e na segunda etapa três professoras que além de atuarem no ciclo I também participaram ativamente do programa. Os dados foram obtidos na fase um por meio de uma entrevista diagnóstica registrada em gravador de voz e das observações e transcrições registradas em vídeo e gravador de voz dos dezesseis encontros do programa de formação continuada realizado em 2013 e a fase dois contemplou observação das aulas das docentes no 2º semestre de 2013, encerrando com uma entrevista final. As manifestações dos professores de educação física no programa, assim como as situações observadas e as entrevistas realizadas apontaram que o perfil dos docentes estão em uma...
Keywords: Abordagem interdisciplinar do conhecimento; Professores - Formação; Educação fisica; Ensino fundamental; Metodo de projeto no ensino; Conscientização; Interdisciplinary approach to knowledge